Impact of anxiety and depression on disease activity and quality of life in patients with lupus nephritis - Ritambra Dadwal; Pragya Pathak; Arunkumar Subbiah; Ujjwal Dahiya (Indian Journal of Psychiatry)
Background of the Study: Lupus is an autoimmune disease that affects multiple body systems and requires long-term treatment. The multisystem effect of this disease and long treatment may cause anxiety and depression in patients with lupus nephritis (LN) and ultimately deteriorate their quality of life and also affects the activity of the disease. Aim of the Study: This study aims to assess anxiety, depression, and quality of life in patients with LN and their relationship with disease activity. Material and Methods: A descriptive cross-sectional study was conducted to assess anxiety, depression, and quality of life among patients with LN. A total enumerative technique was used for the recruitment of 100 patients and data collected using standardized tools were analyzed. Results: The results of the study showed that the majority of patients (60.0%) with LN had moderate anxiety and most of them (61.0%) had moderate depression that affected their quality of life and impacted the disease activity index in lupus. Conclusion: LN patients experience significant levels of anxiety and depression, which deteriorates their quality of life and negatively impacts disease activity. Active surveillance for these conditions and early diagnosis might help in the improvement of health-related outcomes in such patients.